(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Pinalia obesa (Lindl.) Kuntze, Pinalia spicata (D. Don) S. C. Chen & J. J. Wood and Pinalia acervata (Lindl.) Kuntze of the family Orchidaceae have been reported here as new angiospermic record for Bangladesh flora. Detailed examination with description, flowering time, ecology and geological distribution of the species has been provided here with illustration and photographs.